Genome-Wide Polygenic Score and the Risk of Ischemic Stroke in a Prospective Cohort: The Hisayama Study. Issue 3 (March 2020) - Hachiya, Tsuyoshi; Hata, Jun; Hirakawa, Yoichiro; Yoshida, Daigo; Furuta, Yoshihiko; Kitazono, Takanari; Shimizu, Atsushi; Ninomiya, Toshiharu
Abstract : Background and Purpose—: Environmental and genetic factors contribute to the development of ischemic stroke (IS). We recently developed a genome-wide polygenic risk score (PRS) for IS using case-control datasets from 4 large-scale observational studies conducted in Japan. Our objective in the present study was to confirm the association between the PRS and the risk of IS with data from an independent prospective cohort recruited from the general Japanese population. Methods—: A total of 3038 subjects aged ≥40 years were followed up for 10 years (2002–2012). The genome-wide PRS was calculated using genotype data from >350 000 single-nucleotide polymorphisms. The PRS levels were divided into quintiles. High and low genetic risk groups were defined as top 60% and bottom 40% of PRS, respectively. The hazard ratio (HR) for the development of IS was estimated using a Cox proportional hazards model. Results—: During the follow-up period, 91 cases developed first-ever IS. The age- and sex-adjusted HR for IS increased with higher PRS levels ( P for trend, 0.03). Subjects with the highest quintile level of PRS had a 2.44-fold (95% CI, 1.16–5.12) greater risk for IS than those with the lowest quintile level after adjusting for age and sex. A similar association was observed after adjusting for environmental risk factors ( P for trend, 0.03). As compared with low genetic risk group, the age- and sex-adjusted HR in high genetic risk group was 1.63 (95% CI, 1.04–2.55), which was comparable to the HR of hypertension (HR, 1.41), diabetes mellitus (HR, 1.72), and smoking (HR, 1.54). The age- and sex-adjusted HR increased with the number of environmental risk factors in both high and low genetic risk groups without significant interaction. Conclusions—: A high genome-wide PRS was a significant risk factor for IS independent of environmental risk factors in a general Japanese population. This finding suggests that PRS may be useful to identify individuals at a high risk of IS.